(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The integration of student-centered approaches in foreign language education has significantly influenced teaching methodologies, particularly in English language instruction. With the rapid advancement of educational technologies, new opportunities have emerged to enhance language learning experiences by prioritizing individual learning styles, motivations, and engagement. This study explores the role of educational technologies in supporting a student-centered approach to English language teaching, focusing on the context of higher education in Uzbekistan. The research examines how digital tools, interactive platforms, and adaptive learning systems contribute to improving students’ language proficiency, autonomy, and overall learning outcomes. By analyzing various technological applications, including virtual learning environments, artificial intelligence-assisted language tutors, and gamified learning strategies, the study highlights the effectiveness of integrating technology into student-centered language instruction. The findings indicate that the use of technology fosters a more interactive, flexible, and personalized learning experience, leading to improved communication skills, motivation, and knowledge retention. The study concludes with recommendations for educators on implementing technology-enhanced, student-centered English language teaching methods in higher education institutions.